Synthesis and properties of g-C3N4 bulk and nanosheets derived from thiourea - Anh, Luu Thi Lan; Truong, Nguyen Quang; Mai, Nguyen Thi Tuyet; Tu, Nguyen Cong; Cuong, Le Manh (Vietnam Journal of Science and Technology, 2025)
<div class="[–thread-content-max-width:32rem] @[34rem]:[–thread-content-max-width:40rem] @[64rem]:[–thread-content-max-width:48rem] mx-auto flex max-w-(–thread-content-max-width) flex-1 text-base gap-4 md:gap-5 lg:gap-6 group/turn-messages focus-visible:outline-hidden" tabindex="-1"> <div class="min-h-8 text-message relative flex w-full flex-col items-end gap-2 text-start break-words whitespace-normal [.text-message+&]:mt-5" dir="auto" data-message-author-role="user" data-message-id="c604f5bb-005e-46dd-ab56-9bca48ef8c6b"> Graphitic carbon nitride (g-C3N4) is a metal-free polymer semiconductor of interest for visible-light photocatalysis. Here, the g-C3N4 bulk was prepared by thermal polycondensation of thiourea in air (480–550 °C, 2 h; 5 °C min−1). XRD and FTIR analysis confirmed the heptazine/triazine framework, with well-defined (002) and (100) reflections obtained at 520–550 °C, while lower temperatures showed incomplete condensation. Few-layer g-C3N4 nanosheets were then produced by thermal oxidation/exfoliation of the bulk at 500 °C in static air, yielding an expanded, porous morphology observed by FESEM and a weaker (002) peak together with an additional feature near 23°. Optical characterization (UV–Vis DRS and PL) indicated improved light utilization and charge-carrier behavior for the nanosheets: the optical bandgap decreased from 2.750 eV (bulk) to 2.625 eV (nanosheets) and the PL maximum blue-shifted (≈465 → 444 nm) with lower intensity, suggesting suppressed electron–hole recombination. Lorentz deconvolution of PL spectra revealed three main emission centers associated with distinct transition pathways. This simple, solvent-free route using low-cost thiourea provides scalable g-C3N4 bulk and nanosheets for visible-light-driven environmental and energy applications.